The application of ground high-precision magnetic survey to the geology and mineral investigation in Huanghe Town area. Issue 1 (February 2021) - Lu, Yuguo; Xiong, Bin; Wang, Yanhe; Su, Xiaoqin
Abstract: Three projects have been done to investigate the geology and mineral distribution in Huanghe town area A'nyemaqen-Bayanhar orogen, during the year 2013 2017. Ground high-precision magnetic method on a scale of 1:50000 has been used to study the magnetic character of the geological body and rocks. Correction has been taken in order to normalize magnetic anomaly calculated by different zero points. With the understanding of magnetic character, the distribution of stratum and geological structure can be known. After four years' job, 16 faults have been recognized and an acid-intermediate intrusive lithosome has been found.